Dépistage de la violence faite aux femmes. Epreuves de validation et de fiabilité d'un instrument de mesure français. - Brown, J. B. (2001)
OBJECTIVE: To replicate, in a Francophone community, our prior work determining the reliability and validity of the full Woman Abuse Screening Tool (WAST) and a two-item version (WAST-Short). DESIGN: Questionnaires completed by abused and nonabused women. SETTING: Two women's shelters in Francophone communities in Ontario and Quebec and participants' homes or workplaces. PARTICIPANTS: A convenience sample of 25 abused women currently residing in two women's shelters and a convenience sample of 21 women who reported they were not abused. MAIN OUTCOME MEASURES: Women's responses to French versions of the WAST, the Abuse Risk Inventory (ARI), and comfort in answering the questions were compared. Also, the reliability and validity of French versions of WAST and WAST-Short were assessed. RESULTS: Abused (n = 23) and not abused (n = 21) women were demographically similar. A strong single-factor structure that accounted for 81% of total variance in the French WAST items was identified. The French WAST was found to be highly reliable with a coefficient alpha of .95 and demonstrated construct and discriminant validity. The WAST-Short correctly classified all the nonabused women and 78.7% of the abused women. The abused women reported feeling less comfortable responding to the WAST questions than the nonabused women. CONCLUSION: The French version of the WAST demonstrated good reliability and validity and discriminated between known samples of abused and nonabused women. Even though the French WAST-Short did not perform as well as the English version, results of this study support further evaluation of the WAST for screening women in Francophone or bilingual family practice settings.